Formula Optimal dalam Penentuan Aspek Penting pada Desain Alat Pemotong Ring AMDK Gelas Plastik Menggunakan Metode Quality Function Deployment (QFD) - Eko Ari Wibowo; Galih Mahardika Munandar; Muhammad Nur Wahyu Hidayah; Widyastuti (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
Drinking water waste in plastic cups is increasing every year, which has an impact on environmental sustainability, so there is a need for equipment solutions for processing this waste. The aim of this research is a formulation to determine important aspects in the design of ring-cutting tools for plastic cup bottled drinking water. The method used is Quality Function Deployment (QFD) by considering user aspects through Voice of Customers (VoC) with 10 needs. This data is converted into 9 technical data which is analyzed with the House of Quality (HoQ). The results show priority improvements for the development of these tools, namely: manual cutting tool design (46,318), intuitive cutting tool design (45,227), adjustable tool holders and cutters (43,636), portable cutting tool design (33,591), components using standard parts (25,136 ), steel material (25,091), affordable tool manufacturing costs (20,455), non-corrosive material (17,955) and cylindrical and non-slip handle shape (12,273). This data is used as a basis for further research to design this tool. Keywords: Plastic Cups, QFD, Ring Cutting